A DRIVER's Guide to European Repositories: Five studies of important Digital Repository related issues and good Practices - Karen van Godtsenhoven, Kasja Weenink, Leonardus Johannes Maria Waaijers (Amsterdam University Press, 2008)
The Driver's Guide is a practical guide for repository managers and institutions who want to build their own repository.